Assuring Corporate Social Responsibility Reports: Motives and Challenges of Egyptian Companies - Ganna, Mona; Aladwey, Laila (The Arab Journal of Administration, 2025)
This study aims at examining the contemporary practice of Corporate Social Responsibility (CSR) assurance and exploring its future in Egypt. Forty-four managers working in Egyptian listed companies with a recognized CSR experience are surveyed to attain their perceptions on the issues examined. Kruskal Wallis test are utilized for hypotheses testing. Results reveal that the lack of awareness about the assurance importance and its high cost are perceived as the main hindrances of assurance reports in Egypt. Respondents’ level of experience has no impact on their perceptions of the Egyptian companies’ motives of to assure CSR reports. However, the respondents’ experience level influences their realization of certain challenges, such as the dearth of stakeholders’ pressure; the concerns about auditors’ independence and the lack of the awareness of importance of CSR assurance, that may limit Egyptian companies to undertake the assurance decision. Furthermore, respondents’ experience level affect on their perceptions of the urgency of unified reporting guidelines as well as the stakeholders’ pressure to enhance the future of CSR assurance in Egypt. In addition, the companies’ size influences the respondents’ perceptions about the identified factors that stimulates Egyptian companies to assure CSR reports, excluding the need to enhance the external reporting. Also, the companies’ size affects the respondents’ view of stakeholders’ pressure as a factor that imped Egyptian companies from undertaking the assurance decision. Finally, for each identified strand enhance the diffusion of CSR assurance in Egypt, our results report a significant impact of the companies’ size on the respondents’ perceptions.